N-(4-Nitrobenzylidene)-N'-Phenylhydrazine - Tunc, T; Tezcan, H; Sari, M; Büyükgüngör, Orhan; Yagbasan, R (Blackwell Munksgaard, 2003)
Molecules of the title compound (alternative name: p-nitrobenzaldehyde phenylhydrazone), C13H11N3O2, adopt an E configuration about the azomethine C=N double bond. Molecules are approximately planar and the dihedral angle between the planes of the phenyl rings is 11.62 (9)degrees. Hydrogen bonding links molecules related by 42 screw axes to form helices with a pitch of 7.7186 (8) Angstrom.